Physico-mechanical characterization of 3D-printed PLGA for patient-specific resorbable implants in craniofacial surgery - Dimitri Kulker; Julie Pepin; Benoit Rosa; Boris Laure; Mathieu Venin; Jordan Biglione; Arnaud Pare (Scientific Reports)
Abstract Patient-specific implant (PSI) has optimized the management for a wide range of complex craniofacial deformity over the past years by increasing the accuracy of surgical procedures and lowering the operating time. In hypertelorism (HTO) surgery particularly, the orbital bone repositioning is nowadays guided by patient-specific bone fixation plates that are usually made from non-resorbable alloplastic material (e.g., titanium). Developing resorbable personalized plates could be a relevant alternative to overcome the well-known drawbacks of titanium plates such as infection, exposure or even the lack of bone growth which is detrimental in pediatric patients. This study investigated the mechanical and structural characteristics of poly(lactic-co-glycolic acid) (PLGA) PSI as resorbable materials for HTO surgery. We assessed the feasibility of printing PLGA PSI by Fused Deposition Modeling additive manufacturing (FDM). The geometrical and the mechanical properties of the 3D-printed device were compared with standard resorbable plates and analyzed after sterilization process (i.e., hydrogen peroxide gas plasma). The Young’s modulus was greater than the standard resorbable plates while a decrease of 36% (p = 0.004) after the sterilization was observed. The sterilization also induced a plate deformation with an increase of 0.27 mm in Z-axis and a decrease of 0.8 mm in Y-axis due to annealing effect. Compared to the design, the PLGA PSI were successfully 3D-printed with a maximum deviation of 0.1 mm, making our custom-made plate promising for personalized craniofacial applications. Further investigations on the sterilization process must be considered in view of its mechanical and structural impact on resorbable PSI.